THE EFFECT OF EMPLOYEE TRAINING AND DEVELOPMENT ON THE PRODUCTIVITY AND CREATIVITY OF BATIK CRAFTSMEN IN KLAMPAR VILLAGE, PROPPO DISTRICT, PAMEKASAN REGENCY - Zahroh, Fatimatus; Samsuki, Samsuki (Universitas Islam Lamongan, 2025)
Klampar Village, Proppo District, Pamekasan Regency, is known as the center of batik craftsmen on Madura Island. The challenges of globalization and market competition require batik craftsmen to improve their skills and innovation in order to remain competitive. This study aims to analyze the effect of employee training and development on the productivity and creativity of batik craftsmen in Klampar Village. A quantitative approach with a descriptive correlational method is used to measure the relationship between these variables. The research sample consisted of 27 batik craftsmen who had undergone training in the past year, selected using a purposive sampling method. Data collection was carried out through a questionnaire with a Likert scale of 1-5, and data analysis used multiple regression with the help of SPSS 16.0. The results of the study showed that partially, the development variable (X2) had a significant effect on creativity (Y), while training (X1) and productivity (X3) did not have a significant effect. However, simultaneously, the three independent variables contributed significantly to increasing the creativity of batik craftsmen. The classical assumption test showed that the regression model met the validity requirements, with normally distributed data, no multicollinearity, and homogeneous residual variance. These findings emphasize the importance of training and development strategies that not only increase productivity but also encourage creativity in facing market dynamics. This study provides recommendations for stakeholders in designing sustainable human resource development programs for the batik industry in Klampar Village